Teaching undergraduates research skills by doing and reflecting - Douwtje van der Meulen (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article explores what factors contributed to the success of the collection management course and in specific the role of the designed group exercise aimed at teaching undergraduate students basic skills in the scientific research method by doing and reflecting. It finds its explanations in the learning theories of constructivism and constructive alignment.